Impact of co-administration of apricot kernels and caffeine on adult male diabetic albino rats - Nour El-Deen, Ahmed El Sayed; Taha, Ahmad Mohamad; Elsayed, Almoatazbellah; Ali, Ahmed Noaman; Taha, Reda Samir (Frontiers in Physiology, 2024)
The purpose of this study is to evaluate the impacts of apricot kernels and caffeine on blood glucose, lipid profile, insulin secretion and antioxidant effect in diabetic rats. Forty adult male albino rats were divided into five groups: normal control, diabetic control, diabetic treated with apricot kernels, diabetic treated with caffeine and diabetic rats treated with apricot kernels plus caffeine. Fasting samples were collected at the end of the study for analysis, and pieces of liver and pancreatic tissues were removed for histological analysis. There was a significant decrease in blood glucose level, glycated hemoglobin, body weight, total cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C) and a significant increase in insulin and high-density lipoprotein cholesterol (HDL-C) levels in the kernel and caffeine-treated groups. However, there was little histological alteration in the liver or pancreas and no significant difference in the histological findings between groups. Overall, it can be concluded that apricot kernel and caffeine had a positive effect in decreasing blood glucose and harmful lipid profile and that caffeine had a synergetic effect on the apricot kernel.